Molecular Analysis of the EMM Gene of Group a Streptococcus Strain Di323 - Rantty, Rebecca Robert (2001)
The epidemiological studies and characterization of group A streptococci (GAS) are mainly based on serological M and T typing, but although T typing is useful it is not M specific. In addition, it is difficult to prepare the M antisera and the increasing number of new M types makes them non-typeable with the available reference sera. The M protein is a major virulence factor of GAS which is encoded by the emm gene. The 5' ends of this gene are highly heterogenous and encode for specificity of the M serotypes used for M typing. Therefore sequencing of the 5' ends of the emm gene is the choice alternative to the serological typing in the characterization of GAS when M antisera are not available. The Malaysian GAS strain, D 1323 shows unique serotype specificity based on the homology searches of the 5' end emm gene sequence. The emm gene of D1323 was amplified using 'all M' primers and cloned into pCR®2.1-TOPO® vector for its sequence determination as well as into pTrcHis2-TOPO® vector for its expression. Plasmids of positive clones in pCR®2.1-TOPO® were sequenced and the positive clones in pTrcHis2-TOPO® were analysed for protein expression by SDS-PAGE and Western immunoblotting. The complete deduced sequence of the emm gene ofD1323 was shown to contain an open reading frame of 1416 nucleotides which encodes for 429 amino acid residues of the mature M protein. There are three copies of C repeats in the sequence. The cleavage site of a signal peptide was predicted to be located at amino acid residue 42. Conserved regions of the C-terminus which are shared among various M serotypes and that of the leader peptide were also determined based on multiple sequence alignment. The M protein ofD1323 was predicted as M Class I protein based on the alignment of the C-terminus and phylogenetic analysis. The fusion M protein was successfully expressed in the Escherichia coli system and its size was determined.